2011
DOI: 10.1175/2010jamc2367.1
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control and Tilt Correction Effects on the Turbulent Fluxes Observed at an Ocean Platform

Abstract: This study investigates atmospheric factors influencing the quality and the postprocessing (e.g., tilt correction) of fast-response measurements of turbulent fluxes for difficult open-sea measurements over an offshore platform. The data were collected at the Ieodo Ocean Research Station over the Yellow Sea during the period from 5 November 2007 to 19 February 2008. The quality control removal of the data generally depends on wind speed, relative humidity, significant wave height, visibility, and stability. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…For instance, Oh et al . [] recently reported that 40% of their data at the wind speed of 17 m/s failed their quality control procedures. They have suggested this to be a sea‐spray effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Oh et al . [] recently reported that 40% of their data at the wind speed of 17 m/s failed their quality control procedures. They have suggested this to be a sea‐spray effect.…”
Section: Resultsmentioning
confidence: 99%
“…Note that as the wind speed increases, the percentage of data runs affected by the spray also increases and so does the occasional number of data runs which may escape the controls. For instance, Oh et al [2011] recently reported that 40% of their data at the wind speed of 17 m/s failed their quality control procedures. They have suggested this to be a sea-spray effect.…”
Section: Spray Effectsmentioning
confidence: 99%
“…It is clear that the Ogive curve approaches a constant at an averaging period of 10 min, which we chose as the averaging period in our calculation of turbulent fluxes. Coordinate rotation (tilt correction) and detrendingThe coordinate system of the sonic measurements is transformed into the mean‐flow streamlines to eliminate instrument tilt errors and cross contamination among components of the turbulent flux vector [ Finnigan , ; Oh et al ., ]. We applied the double rotation approach [ Kaimal and Finnigan , ] in this work (it is introduced in detail in the ).…”
Section: Data Processing and Quality Controlmentioning
confidence: 99%
“…Those two systems sampled three-dimensional wind components, air pressure, air temperature, and absolute carbon dioxide and water vapor densities at 20 Hz, and then processed to turbulent fluxes, such as latent heat flux, sensible heat flux, momentum flux, friction velocity, and carbon dioxide flux at 30 min intervals using a data logger (CR3000, Campbell Scientific, United States). To cleanse the erratic signals from the original turbulent fluxes, we post-processed them by checking absolute limits and de-spiking in a similar fashion to the method of Oh et al (2010Oh et al ( , 2011. During the analysis period from April to June 2016, the coverage of turbulent fluxes was 59.6% (61.3%) for latent heat flux, 63.9% (62.1%) for sensible heat flux, and 43.2% (51.6%) for friction velocity at the northeastern (southwestern) direction.…”
Section: Observational Site and Socheongcho Ocean Research Station Datamentioning
confidence: 99%
“…To better understand the underlying processes driving air-sea interactions, direct and accurate quantification of the turbulent fluxes over the ocean surface are needed (Garratt, 1992;Paw et al, 2000;Ha et al, 2007;Oh et al, 2010Oh et al, , 2011Yun et al, 2015;Katz and Zhu, 2017). Despite the importance of extensive observational data, most experiments on air-sea interactions are usually limited to short durations and require buoys that are located too close to land, deeming them unsuitable to accurately and explicitly explain oceanic characteristics (Yelland et al, 2009).…”
Section: Introductionmentioning
confidence: 99%